2014
DOI: 10.4269/ajtmh.13-0032
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Diabetes and Impaired Fasting Glucose in Patients with Glucose-6-Phosphate Dehydrogenase Deficiency in the Western Brazilian Amazon

Abstract: Abstract. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the most common human genetic abnormalities, and it has a significant prevalence in the male population (X chromosome linked). The purpose of this study was to estimate the frequency of impaired fasting glucose and diabetes among G6PD-deficient persons in Manaus, Brazil, an area in the Western Brazilian Amazon to which malaria is endemic. Glucose-6-phosphate dehydrogenasedeficient males had more impaired fasting glucose and diabetes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
(4 reference statements)
2
17
1
Order By: Relevance
“…Severe hyperglycaemia could further decrease G6PD activity and expression in human islets [22]. By contrast, another study showed a high prevalence of impaired fasting glucose and diabetes in people with G6PD deficiency [23,24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Severe hyperglycaemia could further decrease G6PD activity and expression in human islets [22]. By contrast, another study showed a high prevalence of impaired fasting glucose and diabetes in people with G6PD deficiency [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…She was found to have hyperglycaemia with mild to moderate dehydration, but there was no evidence of diabetic ketoacidosis. Her venous pH was 7.4 (7.35-7.45), P CO2 was 0.59 (0.47-0.6) kPa, HCO 3 was 25.8 (22)(23)(24)(25)(26) mmol/L, plasma glucose was 25.5 mmol/L, acetone negative, urine ketone +1 and HbA 1c was 132 mmol/mol (14.2%).…”
Section: Case Reportmentioning
confidence: 99%
“…[47] Whether reduced erythrocyte metabolism in G6PD deficiency[48] could be partly due to lower adrenal androgens has not been previously been considered. Nevertheless such a hypothesis would provide an underlying explanation for G6PD deficiency, or other exposures, such as statins, having different associations with cardiovascular disease[4, 16, 17] and diabetes,[1014] because androgens have different effects on cardiovascular disease[49] and glucose metabolism,[50, 51] as well as potentially representing the evolutionary biology trade-off of survival (here from malaria) against reproductive success consistent with life-history theory. [3]…”
Section: Discussionmentioning
confidence: 99%
“…[8] G6PD deficiency can also result in hyperbilirubin which could cause brain damage and dysfunction. [9] G6PD deficiency has been reported as associated with a higher risk of diabetes in a large cross-sectional study from Israel using medical records[10] and several small hospital-based case-control studies,[1014] although not in a small study from Italy. [15] G6PD deficiency has also been associated with lower risk of cardiovascular disease mortality in two cross-sectional studies from Sardinia (Italy),[16, 17] and with lower risk of myocardial infarction in a case-control study,[4] although associations of G6PD deficiency with cardiovascular disease risk factors[18, 19] and all-cause mortality[17, 20] are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency is believed to be caused by mutation in the G6PD gene, an X-linked hereditary genetic defect [3] often predominant in males [4]. Reports have shown that about 400 million people are affected worldwide and it is highly polymorphic [5]- [7]. The prevalence of G6PD disorder has been reported in many areas of the world including the Middle East [8] [9].…”
Section: Introductionmentioning
confidence: 99%